Pengaruh Lingkungan Terhadap Penyalahgunaan Narkoba dan Regulasinya - Rusli, Tami; Jonathan, Ahmad Kevin; Rinaldo, M; Al Hadusi, Rafli; Bodhi, Arya (Journal of Law, Education and Business, 2025)
Drug abuse is a serious problem that has a wide impact on health, social, and legal aspects. This study aims to analyze the influence of the environment on the tendency of drug abuse and to examine the effectiveness of regulations implemented as prevention and control efforts. Social environments such as family, peer groups, and community conditions play a major role in shaping individual behavior. Individuals who grow up in an environment with weak supervision, negative peer influence, and minimal education about the dangers of drugs tend to be more vulnerable to abuse. This study uses a qualitative method with a case study approach and analysis of laws and regulations related to narcotics in Indonesia, especially Law Number 35 of 2009 concerning Narcotics. The results of the study show that although regulations are available and quite strict, their effectiveness is greatly influenced by implementation in the field and the active role of the social environment. Therefore, efforts to prevent drug abuse do not only depend on the legal aspect, but also require the involvement of a positive and supportive environment.